Evaluation of the effect of sodium hypochlorite on the transverse strength of acrylic denture base resin (Mustansiria Dental Journal, 2018)
This study evaluated the transverse strength of polymerized acrylic resin afterimmersion in sodium hypochlorite (NaOCl) for 20 minute, 3times a day for 15 days.40 rectangular specimens were prepared from heat polymerized acrylic resin; 20specimens were immersed in 0.5℅ NaOCl as experimental group and 20 specimenswere immersed in distilled water as control group. The transverse strength wasmeasured using a 3 –point bending test in a universal testing machine. The studyshowed that there was no statistically significant differences (p>0.05) between groups.It may be concluded that immersion in NaOCl solution did not influence thetransverse strength of heat polymerized acrylic resin.